Healthcare as a Human Rights Issue Normative Profile, Conflicts and Implementation - Klotz, Sabine; Bielefeldt, Heiner; Schmidhuber, Martina; Frewer, Andreas (Menschenrechte in der Medizin / Human Rights in Healthcare, 2017)
This book deals with various facets of the human right to health: its normative profile as a universal right, current political and legal conflicts and contextualized implementation in different healthcare systems. The authors come from different countries and disciplines - law, political science, ethics, medicine etc. - and bring together a broad variety of academic and practical perspectives. The volume contains selected contributions of the international conference "The Right to Health - an Empty Promise?" held in September 2015 in Berlin and organized by the Emerging Field Initiative Project "Human Rights in Healthcare" (University of Erlangen-Nürnberg).